The impact of information provision on public willingness to use recycled water for flushing from the perspective of risk perception - Ding, Yizhe; Liu, Xiaojun (Frontiers in Environmental Science, 2024)
To solve the current urban water shortage, increasing the willingness of urban residents to use recycled water for flushing is one proposed approach. This study developed a risk perception measurement model of recycled water for toilet flushing to explore which risk triggered people’s risk perception of recycled water, and then analyzed the interaction among information provision, trust, risk perception, and willingness to use recycled water. The main results were as follows. First, the risk perception of recycled water for flushing mainly come from four types of risks, which were performance risk, health risk, service risk and financial risk in order of importance. Second, reducing the perceived risk can improve public willingness to use recycled water for flushing, and greater trust in the water authorities and recycled water enterprises reduces the public’s perception of the risk of recycled water. A higher level of initial trust is related to higher willingness to use recycled water. Third, information provision can enhance the risk perception of recycled water and enhance trust in the water authorities and recycled water enterprises, but information provision does not directly affect the willingness to use recycled water. This indicates that reducing performance risk and health risk of recycled water, will be the key to controlling the overall risk perception of recycled water and promoting willingness to use. Effective risk communication strategies combine information provision and trust in information providers, which together affect risk perception and thus the willingness to use recycled water.